Dynamics of Utilization and Sustainable Production Potential of Narrow-barred Spanish Mackerel (Scomberomorus commerson) in the Waters of Tanjung Jabung Barat Regency, Jambi - Dyva Mahda Wahyuni; Lauura Hermala Yunita; Rahayu Dian Eka Putri; Hari Cahyono; Giri Pratama; Diah Maulani Saputri (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Narrow-barred Spanish mackerel (Scomberomorus commerson) is a high-value large pelagic fish resource extensively exploited by fishers in Tanjung Jabung Barat waters, Jambi Province. This study aimed to analyze the Maximum Sustainable Yield (MSY) and utilization rate of mackerel based on production and fishing effort data from 2019 to 2023. The Schaefer surplus production model was applied with fishing effort standardization using the Fishing Power Index (FPI). Fishing gears operating in the area included a lift net (bagan perahu), hand line, group purse seine, one boat purse seine, bottom long line, and troll line. Group purse seine was selected as the standard gear with a CPUE of 525.83 kg/unit. The MSY was estimated at 60,753.94 kg year⁻¹ with an optimum fishing effort (Eopt) of 208.98 standardized units. The Total Allowable Catch (TAC) was 48,603.15 kg year⁻¹ (80% MSY). The average utilization rate over the study period was 22.76%, and the average effort rate was 12.58%. All utilization and effort rates were below 60%, indicating underfishing. This condition suggests there is still potential for sustainable increases in fishing effort in these waters